THE MODERN WOMEN STORYTELLER OF MUSLIM INDIA AND PAKISTAN: HIJAB IMTIAZ ALI - Davut ŞAHBAZ (International Journal of Eurasia Social Sciences, 2017)
Hijab Imtiaz Ali was born on November 4, 1915 in Hydrabad India as a daughter of an aristocratic family. The author started writing in childhood. She was a critical thinker and activist. Nature, women, psychology and love were the main themes of her works and these works have been published in renowned magazines. Hijab Imtiaz Ali ushered the feminist style in Urdu Literature. In addition to literature, she has led women in different fields. She was the first Muslim woman pilot in Muslim India and Pakistan. After married to novelist Imtiaz Ali Taj, Hijab moved to Lahore and died in 21 May 1999 in this city.